STUDENTS’ PERCEPTIONS AND CHALLENGES ON PEER FEEDBACK OF EFL UNIVERSITY STUDENTS’ WRITING - Kurniawati, Heny Nursela (RETAIN, 2021)
Peer feedback is an excellent tool to improve the students’ writing performance. Also, peer feedback often considered as an important learning strategy. In this view, the aims of the study are to identify two things related to the EFL university students’ perceived and challenges in the implementation of peer feedback in their learning process as an evaluation to the development of peer feedback learning strategy that is used for the future, especially in the field of improving the implementation of the learning process. This research design was a basic qualitative study that explores the students’ experiences in a particular phenomenon. In addition, the researcher used an open-ended questionnaire and semi-structured interview instruments to obtained the data. The subject of the study involved 15 EFL university students of English Department in Surabaya, East Java. The technique that is used to conducted this research was purposive sampling. The result of the study revealed that (1) The EFL university students gave positive perceptions toward peer feedback implementation. The EFL university perceived that peer feedback give various benefits, views, also suggestions to the EFL university students’ writing performance. Then, involving the EFL university students in peer feedback implementation could raise awareness of their writing performance, monitoring, evaluating, and developing their own goal and plan of learning. (2) The challenges faced by the EFL university students becomes a shared experience by the EFL university students’ who involving in peer feedback as the learning process. These proved that peer feedback implementation is the truly valuable tool for improving writing performance. The conclusion and suggestion for teacher, educator, or teaching staff and future research are discussed.